Physiotherapy management of minimally invasive Oxford medial compartment knee arthroplasty: an observational study of 100 patients following an accelerated treatment protocol - Jenkins, C; Barker, K; Reilly, K; Pandit, H; Dodd, C; Murray, D (2006)
Objectives: To describe an accelerated protocol for early discharge of patients undergoing Oxford medial unicompartmental knee arthroplasty using a minimally invasive approach. Design: Prospective observational study. Setting: Specialist orthopaedic National Health Service hospital. Participants: One hundred consecutive patients (40 female, 60 male) undergoing Oxford medial unicompartmental knee arthroplasty with an average age of 64 (range 44-80) years. Outcome measures: Oxford knee score, American Knee Society score (objective and functional) and the ability to perform functional tasks were recorded pre-operatively and 6 weeks and 1 year postoperatively. Success was taken as an improvement in these scores or as an increased ability to perform functional tasks. Results: Satisfactory results were attained after accelerated discharge, with the mean objective American Knee Society score increasing from 41/100 (95% confidence interval 38.0-44.5) pre-operatively to 87/100 (95% confidence interval 83.1-90.3) at 1 year, and the Oxford knee score increasing from 24/48 (95% confidence interval 21.9-25.2) to 41/48 (95% confidence interval 39.6-42.8) over the same period. All monitored functional activities improved. The mean values before surgery and 6 weeks and 1 year after surgery are presented. Conclusion: Outcome following minimally invasive Oxford medial unicompartmental knee replacement is not compromised with the use of an accelerated treatment protocol. © 2006 Chartered Society of Physiotherapy.